A Segmentation Algorithm for the Leaf Area Identification in Plant’s Images - Gupta, Abhishek (Science & Technology Asia, 2022)
The agricultural field is emerging for solving problems using computer vision algorithms. To monitor the plants based on leaf segmentation is also one of the essential requirements in the near future where there will be no manual work for the cultivation and growth of the plants. In this paper, an algorithm is proposed for the automatic monitoring of the plant based on leaf segmentation. The proposed algorithm does not take much time and also is recommended to use in real-time monitoring. The algorithm was validated on two databases and results were found satisfactory to use it for monitoring purposes. A method of plant monitoring based on leaf segmentation is also discussed for the future enhancement of this work. The combination of the proposed algorithm and method of monitoring will aid in designing a fully automated system for the monitoring of plants.